2019
DOI: 10.1007/s12028-019-00826-0
|View full text |Cite
|
Sign up to set email alerts
|

Review: Post-Intensive Care Syndrome: Unique Challenges in the Neurointensive Care Unit

Abstract: Within the last couple of decades, advances in critical care medicine have led to increased survival of critically ill patients, as well as the discovery of notable, long-term health challenges in survivors and their loved ones. The terms post-intensive care syndrome (PICS) and PICS-family (PICS-F) have been used in non-neurocritical care populations to characterize the cognitive, psychiatric, and physical sequelae associated with critical care hospitalization in survivors and their informal caregivers (e.g., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
46
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 140 publications
(207 reference statements)
0
46
0
5
Order By: Relevance
“…patients is a primary specialization in LTACHs, which have experienced critical care clinicians and respiratory therapists in an accredited acute care hospital setting. 7 Patients with COVID-19 can develop post-ICU syndrome [8][9][10][11] or chronic critical illness that requires more intensive and prolonged hospitalization, as well as specialized interventions. 12 Although LTACH staff have the skills necessary for treatment of COVID-19 patients, extensive preparations and transformations are required for treating patients with a highly virulent virus.…”
mentioning
confidence: 99%
“…patients is a primary specialization in LTACHs, which have experienced critical care clinicians and respiratory therapists in an accredited acute care hospital setting. 7 Patients with COVID-19 can develop post-ICU syndrome [8][9][10][11] or chronic critical illness that requires more intensive and prolonged hospitalization, as well as specialized interventions. 12 Although LTACH staff have the skills necessary for treatment of COVID-19 patients, extensive preparations and transformations are required for treating patients with a highly virulent virus.…”
mentioning
confidence: 99%
“…Post-intensive care syndrome is a described phenomenon in critically ill patients [ 65 ], and the neuropsychological impact of critical illness is also seen in ECMO patients with or without overt neurologic injury. Although their 36-Item Short Form Survey psychological domain is comparable to the general population [ 66 ], studies have identified that patients surviving to 6-month follow-up or longer have persistent emotional and mental health difficulties [ 61 , 66 68 , 69 •, 70 ]: depression (20–42%), anxiety (20–55%), and post-traumatic stress (PTS) symptoms (5–47%).…”
Section: Neurocognitive Outcomes Following Ecmomentioning
confidence: 99%
“…Return to work is only seen in 50–65% of patients receiving ECMO for ARDS [ 61 63 ]. Moreover, informal caregivers (often family members) suffer from increased rates of depression, anxiety, and PTS disorders as well [ 65 ], with significant correlation between mental health sequelae in patients and their informal caregivers following VV ECMO for ARDS [ 69 •]. These rates of neuropsychological sequelae may not differ substantially when compared with survivors of severe ARDS without ECMO [ 70 ], but they do highlight the need for intense follow-up that includes physiological and psychological evaluation and support for patients and their loved ones [ 71 ].…”
Section: Neurocognitive Outcomes Following Ecmomentioning
confidence: 99%
“…The BI score at ED visit is a strong independent predictor of allcause 30-day mortality in patients with acute heart failure admitted to ED [24,30], and our results showed that pre-ADL level was also a strong predictor of post-ADL level. For young and physically fit patients, ICU/CCU admission may lead to unnecessary rest or restriction and post-intensive care syndrome [31], counteracting the beneficial effect of rapid ICU-level intervention. These results suggest that pre-ADL level can be a useful tool for the triage of ADHF patients to ICU/CCU admission.…”
Section: Plos Onementioning
confidence: 99%